A novel emotion profiling based on CMAC-Based computational models of affects - Hamwira Sakti Yaacob (2015)
Mental health has become a global concern because of the increasing number of cases related to mental illnesses over the years which places heavy burdens on the global societal well-being and economic growths. In general, mental health is always associated with the states of emotion which can be measured based on several affective dimensions. Emotion plays an important role in various aspects of human daily lives. It can be captured and measured from various responses, such as self-assessment, automatic nervous systems (ANS) responses, facial expressions, voice, speech text, body language and posture and the brain states. Although emotion can be easily acted, it is hardly detected through other forms of emotional expressions. However, such fraudulent is more apparent through the neurophysiology manifestations. The studies of emotion through neurophysiology manifestations are mostly analyzed using various brain imaging devices. Nevertheless, such studies require complex neuroscientific and mystifying cognitive science expertise, which are also rare and expensive. Thus, it can be quite challenging to operate such devices on certain groups of subjects including children under 12 years old. Therefore, in this research, electroencephalography (EEG) is employed due to its simplicity and lower cost. EEG is also used to capture brain temporal dynamic up to millisecond precision, which may not be possible with other brain imaging techniques. Thus, several computational models have been developed to understand emotional states from EEG signals analysis. However, it has been observed that the existing models do not consider both the temporal and spatial dynamics of EEG signals. Hence, the results are inconsistent, especially for subject independent analysis. Therefore, a new emotion profiling technique that aims to provide better performance for understanding and distinguishing different emotional states from EEG signals is introduced in this research. The new model is constructed based on a computational model of cerebellar known as the Cerebellar Model Articulation Controller (CMAC), because it is imbued with similar qualities of self-organizing and non-linearity which are also observed in the neural processes as captured by EEG. A component of CMAC architecture is also utilized to capture spatial dynamic, as well as temporal dynamic of EEG input. Thus, the new model is termed as the CMAC-based Computational Models of Affects (CCMA). The research methodology consists of five phases including awareness of problem, design, development, evaluation and conclusion. With that, the objectives of this research are to design, develop and analyze the CMAC-based Computational Models of Affects (CCMA). Validation of CCMA and the benchmarking models are based on the classification accuracy for subject-dependent homogenous memory profiling, subject-dependent homogenous cross validation profiling, subject-dependent heterogeneous memory profiling, subject-dependent heterogeneous cross validation profiling and subject-independent profiling. The results show that the CCMA is comparable with other models for subject-dependent analysis. In addition to that, it outperforms the others in subject-independent case. In conclusion, it is rationalized that the CCMA is not only viable as a classification model but it is also envisaged to have several potentials for future works.